Problematika Muallaf Dalam Melaksanakan Ajaran Agama Islam Di Desa Tumbang Runen Kecamatan Kamipang Kabupaten Katingan - Supriadi Supriadi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Muallaf is a new convert to Islam and his faith is still very weak and requires consolidation in his new religion. Therefore the need for guidance for the converts, so that kedepanya still better and remain firm aqidahnya in Islamic teachings. The formulation of the problem in this research is how problematic faced by the muallaf family in implementing Islamic teachings and how to overcome the problems faced by the muallaf family in implementing the Islamic teachings in the village of Tumbang Runen Kamipang District Katingan Regency. This study aims to determine how the problems faced by the mufallaf family in implementing Islamic teachings and how to overcome the problems faced by the family of muallaf in implementing Islamic teachings in the village of Tumbang Runen Kamipang district Katingan regency. This research is a qualitative research, the data collected in the form of words that use some data collection techniques that include interview techniques, observation and documentation. Subjects in this study are 5 people convert. The results showed that the problem of muallaf in implementing the teachings of Islam in the village tumbang runen kamipang district katingan district of the data collected muallaf families facing problematics in implementing Islamic teachings, especially the pillars of Islam which is a problem of the family of muallaf especially the sense of lazy in performing prayers and fasting Ramadan, lack of awareness from the hearts of the converts, the hesitation in carrying out the obligations, taking the time to carry out the obligations and looking for compatibility in studying the teachings of Islam.